The effect of microencapsulation of microbial oil containing CLA by the complex coacervation on the physicochemical and sensory characteristics of buttermilk - Samin Rafi Azari; Mohammad Hojjatoleslamy; Zeinab E. Mousavi; Hossein Kiani; Sayed Mohammad Ali Jalali (Food Chemistry Advances)
Conjugated Linoleic Acid (CLA) is known for their positive impact on reducing various diseases, including cardiovascular diseases and blood lipid levels. This study aims to produce enriched buttermilk with stable physicochemical properties via complex coacervation. To address the inherent instability of oils in liquid systems, microcapsules were prepared using sodium alginate and xanthan gum, with optimization achieved through the response surface method (RSM). The buttermilk, enriched at optimal levels of 0 %, 0.04 %, 0.07 %, and 0.1 %, was then incubated at 48 °C for 42 days. Under the optimized conditions, the choice and quantity of gums used for enrichment significantly influenced the properties of the enriched buttermilk. A decrease in pH, along with an increase in acidity, led to enhanced viscosity in the buttermilk. The flow behavior of the buttermilk exhibited pseudoplastic characteristics. Enrichment caused an increase in particle size, with only minimal changes in odor, taste, and color parameters, while the buttermilk remained free from protein agglutinates. Chromatography results showed an increase in unsaturated fatty acids after enrichment. In summary, this study demonstrates the feasibility of producing nutritionally enriched buttermilk with high stability and desirable sensory characteristics. The recommended concentrations for enrichment are 0.04 % and 0.07 %.